(untitled) (Circe de clásicos y modernos, 2020)
The aim of this study is to analyze a potential new fragment of Quaestiones in Exodum in the recently discovered Homiliae in Psalmos of Origen. To make this case, I will first weigh the evidence for and against a Philonic provenance for the tradition cited by Origen (whether paraphrase or citation). I will then offer some lexical, thematic, and form-critical considerations, which suggest that Origen is citing a Philonic interpretation from the Quaestiones rather than paraphrasing the Allegorical Commentary.